2016
DOI: 10.3109/10428194.2015.1063148
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic hematopoietic stem cell transplant overcomes poor prognosis of acute myeloid leukemia with myelodysplasia-related changes

Abstract: Recent studies have shown that acute myeloid leukemia with myelodysplasia-related changes (AML-MRC) exhibits a worse clinical outcome than AML not otherwise specified (AML-NOS). However, transplant outcomes of patients with AML-MRC have not been reported compared to patients with AML-NOS. We analyzed transplant outcomes among 147 patients with AML-MRC or AML-NOS who underwent allogeneic hematopoietic stem cell transplant (allo-HSCT) in a single institution. There were no significant differences in the 2-year o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…Following the recommendations for allo-SCT in patients with AML with intermediate or poor cytogenetic risk [11,12], most fit patients with AML-MRC undergo allo-SCT. Because AML-MRC is a heterogeneous disease, transplantation outcomes in these patients can be highly variable; however, data on transplantation outcomes in patients with AML-MRC are sparse [13], and detailed transplantation outcomes in a largescale cohort fulfilling the WHO classification criteria for AML-MRC have not been reported. Therefore, the prognostic factors for patients with AML-MRC undergoing allo-SCT remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Following the recommendations for allo-SCT in patients with AML with intermediate or poor cytogenetic risk [11,12], most fit patients with AML-MRC undergo allo-SCT. Because AML-MRC is a heterogeneous disease, transplantation outcomes in these patients can be highly variable; however, data on transplantation outcomes in patients with AML-MRC are sparse [13], and detailed transplantation outcomes in a largescale cohort fulfilling the WHO classification criteria for AML-MRC have not been reported. Therefore, the prognostic factors for patients with AML-MRC undergoing allo-SCT remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the patient received azacitidine as consolidation chemotherapy. Allogeneic HSCT is the only curative therapy for AML-MRC (15). Myeloablative conditioning regimens, especially those including total body irradiation, can cause serious mucosal injury (11).…”
Section: Discussionmentioning
confidence: 99%
“…Two single-institution studies from Japan have demonstrated similar OS, non-relapse mortality (NRM), and cumulative incidence of relapse (CIR) between patients with and without MRC. In the first study by Ikegawa et al, out of 139 patients, 60 patients with MRC experienced similar 2-year OS, CIR, and NRM rates of 48%, 37%, and 19%, respectively, while patients without MRC experienced rates of 59%, 35%, and 13%, respectively [45]. AML-MRC was not an independent prognostic factor for poor outcomes after alloHSCT in multivariate analysis (p = 0.7).…”
Section: Allogenic Hematopoietic Stem Cell Transplant (Allohsct)mentioning
confidence: 92%
“…AlloHSCT is advised for all patients with AML-MRC and remains the only known potentially curative therapy in this patient population [45]. Indeed, alloHSCT may be the "great equalizer" for patients with AML-MRC as alloHSCT has been shown to potentially offset the poor prognostic factors associated with the underlying aggressive disease biology.…”
Section: Allogenic Hematopoietic Stem Cell Transplant (Allohsct)mentioning
confidence: 99%